Effect of relaxation processes during deformation on electrical resistivity of carbon black polypropylene composites - A. V. Markov; K. S. Tarasova; V. A. Markov (Тонкие химические технологии)
Objectives. To study the relationship between bending deformation and the change in the electrical resistance of carbon black polypropylene composites.Methods. Conductive polypropylene composites filled with carbon black UM-76 were investigated. The samples were deformed and kept under constant bending at temperatures of 20–155 °C.Results. The deformation of the samples led to a reversible increase in their electrical resistance, while subsequent holding of the samples in the deformed state was accompanied by an exponential drop in their electrical resistance. The average times and activation energies of the electrical relaxation of the deformed polypropylene composites were calculated (30–32 kJ/mol) and compared with similar characteristics of polyethylene composites (15–16 kJ/mol).Conclusions. The electrical resistance relaxation of deformed carbon black polypropylene composites at elevated temperatures is similar to their stress relaxation. The average times and activation energies of the electrical relaxation of deformed polypropylene composites are comparable with similar data on their mechanical relaxation. It was found that these electrical and mechanical phenomena are based on the same underlying physical processes.